The Effect of Packet Tracer Simulator Media on Motivation and Learning Outcomes of Basic Network TKJ Students of Cokroaminoto Vocational School, Kotamobagu - Atjo, Muhammad Fadly; Olii, Djami; Manggopa, Hiskia; Rompas, Parabelem Tino Dolf (JR Education, 2023)
Abstract – The aim of this study was to determine the effect of packet tracer simulator media on the motivation and learning outcomes of basic network students TKJ SMK Cokroaminoto Kotamobagu. Method used _ in study this is quasi experiment or experiment pseudo . Data collection techniques using documentation , questionnaires , and tests whereas technique data analysis using SPSS 26.0 assistance . Research results show that there is positive and significant influence in the use of Cisco media package Tracer to motivation and outcomes student learning on basic network learning at Cokroaminoto Vocational School Kotamobagu . this _ is known from Independent test results Sample T-Test. Obtained Sig.(2-tailed) value of 0.000 <0.05 so could concluded that there is influence positive and significant in use of Cisco Packet Tracer media against motivation study students on learning network elementary school at Cokroaminoto Vocational School Kotamobagu . Whereas from Independent test results Sample T-Test. Obtained Sig.(2-tailed) value is 0.0 0 1 < 0.05 so could concluded that use of Cisco Packet Tracer capable media increase results study student class X TKJ at SMK Cokroaminoto Kotamobagu . Research results show class _ control with total respondent as many as 27 have a mean of 7 0 , 37 and in class experiment with total Respondents 27 had a mean of 7 9.00 . On the Independent Sample Test obtained Sig.(2-tailed) value is 0.000. Because the sig.(2-tailed) value is 0.000 <0.05, there is a significant difference in learning motivation in the two classes. And on class control with total respondent as many as 27 have a mean of 8 0.3 7 and in class experiment with total respondent 27 has mean 8 7 , 22 . On the Independent Sample Test obtained the value of Sig.(2-tailed) is 0.00 1 . Because the value of sig.(2-tailed) 0.00 1 <0.05, there is a significant difference in learning outcomes in the two classes. It can be seen that the better the students' mastery of the packet tracer simulator media, the motivation and student learning outcomes are increasing.